In vivo time‐sequential histological study focused on melanocytes: suggestion of golden time for intervention to prevent post‐laser pigmentary changes. (2nd March 2015) - Song, H.S.; Park, J.‐Y.; Kim, S.J.; Kang, H.Y.
Abstract: Background: Post‐inflammatory pigmentary changes after laser treatments are challenging adverse effect. Objective: To suggest an ideal time period with regard to intervention to prevent post‐laser pigmentary changes, an in vivo time‐sequential histological study focused on melanocytes was performed. Methods: The back skin of four volunteers was irradiated with Q‐switched alexandrite laser (QSAL). In one subject (subject 4), topical corticosteroid was applied onto the irradiated skin from the time of irradiation to day 28. In all subjects, time‐sequential skin biopsies were performed at baseline, an immediate time after irradiation, day 2, day 7, and day 28. Histological and immunohistochemical analyses were conducted. Results: Q‐switched alexandrite laser led to the successful removal of pigments and most melanocytes from the epidermis in all subjects. At day 28, there was increased epidermal pigmentation in the skin of the subjects 1–3. It was noted that numerous activated melanocytes appeared on day 7, continued to be observed until day 28. However, in the subject 4, the melanocyte activation and post‐laser pigmentary changes were not observed. Conclusion: In regard to intervene melanocyte activation, at least 1 week after laser treatment is suggested as a 'golden' time period to prevent pigmentary changes.